2009
DOI: 10.1128/aac.01026-08
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Combinations against Simulated Candida albicans Endocardial Vegetations

Abstract: The in vitro effects of flucytosine (5FC), liposomal amphotericin B (L-AmB), and micafungin (Mica) combinations against two Candida albicans strains that simulated 24-hour-old endocardial vegetations were studied. Mica was superior to 5FC or L-AmB, and the 5FC-L-AmB-Mica combination was superior to all other treatments for one strain but no different from the dual combination of L-AmB-Mica for the other strain.Candida species can adhere to cell surfaces and form a three-dimensional community of microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…By contrast with the previous study in 2008, they measured the antifungal effects only at one time point and used the standard definition of synergism. These data revealed that micafungin was uniquely active against mature C. albicans biofilms, while flucytosine was not [46]. This is in contrast to the data in the previous report, where flucytosine was markedly active against C. albicans biofilms [45].…”
Section: Antifungal Combination Therapycontrasting
confidence: 91%
See 2 more Smart Citations
“…By contrast with the previous study in 2008, they measured the antifungal effects only at one time point and used the standard definition of synergism. These data revealed that micafungin was uniquely active against mature C. albicans biofilms, while flucytosine was not [46]. This is in contrast to the data in the previous report, where flucytosine was markedly active against C. albicans biofilms [45].…”
Section: Antifungal Combination Therapycontrasting
confidence: 91%
“…The triple combination of flucytosine/liposomal amphotericin B/micafungin was superior to all other treatments for one isolate but not different from the dual combination liposomal amphotericin B/micafungin for the other isolate. Although no clear pattern of interaction between these agents was seen, the superior activity of micafungin against 24h-old C. albicans biofilms relative to flucytosine and liposomal amphotericin B was apparent for both isolates [46]. In conclusion, and supported by earlier reports [19], these data demonstrated the activity of echinocandins when used alone or in combination with polyenes against C. albicans biofilm.…”
Section: Antifungal Combination Therapysupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies support the combination of echinocandins with other antifungal drugs to treat C. albicans biofilms (Bink et al, 2011;Kuhn et al, 2002b;Pai, 2009). For example, synergy effects were found for micafungin and fluconazole, voriconazole or liposomal amphotericin B against Candida species (Espinel-Ingroff et al, 2009;Nishi et al, 2009;Olson et al, 2005).…”
Section: Combining Antimicrobial Agents Therapymentioning
confidence: 92%
“…Combination therapy with liposomal amphotericin B plus flucytosine is currently recommended for the treatment of Candida endocarditis [5]. However, it is worth noting that some experimental data showed that the addition of an echinocandin (micafungin) to the combination of liposomal amphotericin B plus flucytosine may be even more fungicidal against simulated C. albicans endocardial vegetations than the combination of liposomal amphotericin B plus flucytosine [46]. This support the idea that a combination therapy with three antifungal agents characterized by different mechanisms of action might improve current treatment of Candida endocarditis, which is a highmorbidity and -mortality disease.…”
Section: Candida Endocarditismentioning
confidence: 99%